Norhayati Abdullah Enterprise / Nadhirah Sharudin … [et al.] - Sharudin, Nadhirah; Mohd Abdul Shukor, Nurul Amira; Mohd Azam, Nurul Amirah; Kamarudin, Siti Norliyana; Sapari, Syazira Nurfadila (2022)
Norhayati Abdullah Enterprise is a family business established by Mrs. Norhayati in 2014. Norhayati Abdullah Enterprise has a total of 4 workers who work under her and sometimes her two (2) children also will help with the business. They are located in Jalan Cemara 1, Bandar Putra which is near the owner's house. The main activity of this business is selling food. Mrs. Norhayati chooses to sell food because cooking is one of her hobbies and it is one of the ways for her to release her stress. When she decided to open her business, she resigned from her old work that give so much pressure on her. Starting with only selling Nasi Lemak, Nasi Ambeng, Soto, and a few types of kuih, she increases the menu with the request from customers and now she has more than 10 menus. Almost 8 years open her roadside stall, she already has a few loyal customers that will always buy food from her stall every morning. As for the case study, we conduct an interview with Mrs. Norhayati, the owner of Norhayati Abdullah Enterprise to collect her business information to identify the nine (9) elements of the Business Model Canvas (BMC) that has been practice by Norhayati Abdullah Enterprise. The major problem that has been identified during the interview is that Norhayati Abdullah Enterprise faces more losses during Pandemic Covid-19 because of the Movement Control Order. Each solution made by Mrs. Norhayati and the solution that we recommend have their own advantages and disadvantages such as the major problem that Norhayati Abdullah Enterprise faces is they do not have any skills in advertising and marketing, we recommend for her to learn more about marketing, especially online marketing. The advantage is the business can be recognized not only in Bandar Putra, Johor but it may be recognized worldwide